PROBLEMS FOR THE DEVELOPMENT OF LEGISLATION REGULATIONS IN INDONESIA - Asri Agustiwi (International Journal of Social Science, 2022)
This article is a discussion of problems related to the preparation of existing laws and regulations in Indonesia, where many of the formations seem rushed, the procedures/formalities are only carried out as a formality. The methodology used is a normative study, which focuses on the legal approach. Other data sources used are articles and journals. The results of the study that can be concluded that the preparation of Legislation is regulated in Law Number 12 of 2011 concerning the Formation of Legislation, where there is regulated how the procedure/systematic of its formation, the principles are contained in Article 5, also the content material is in Article 10. There is a need for greater involvement by the community, because the principle of openness, which is still lacking, moreover the impact of the law made on the community, must also provide benefits to the community. The number of laws and regulations that are formed if the visit is canceled is considered a legal product made by the government is not good, for that utilizing virtual media can increase public trust and participation in the formation of existing laws and regulations in Indonesia.